ANALISIS PERAN BURSA KERJA KHUSUS (BKK) DALAM PENGAMBILAN KEPUTUSAN KARIER SISWA SMK NEGERI 1 SURAKARTA - budi, dyah (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2014)
The objectives of this research are to investigate: (1) the efforts done by Special Job Fair of State Vocational High School1 of Surakarta to improve the job absorption rate of its graduates in the work world; (2) the constraints encountered by Special Job Fair of State Vocational High School1 of Surakarta in conducting its role to improve the job absorption rate of its graduates in the work world; and (3) the solutions taken by Special Job Fair of State Vocational High School 1 of Surakarta in dealing with the constraints to the implementation its role to improve the job absorption rate of its graduates in the work world. This research used the qualitative method with the case study approach. the sources of research data were informants, places, documents, and archives. The results of the research are as follows: 1) The efforts done by Special Job Fair of State Vocational High School 1 of Surakarta to improve the job absorption rate of its graduates in the work world include establishing cooperation with companies of the business world and the industrial world by enhancing the links for channeling its graduates to work world, drawing the students? attentions to work by displaying the profiles of companies, inviting the representatives of companies to the school, improving the hard and soft skills of its graduates, and establishing networks with other special job fairs of other schools in Surakarta City and its vicinity, and establishing cooperation with Indonesian Manpower Agencies. 2) The constraints encountered by Special Job Fair of State Vocational High School 1 of Surakarta in channeling its graduates to work world are students? labile personalities, difficulty in extending information to its students, and the mismatch between the work world and its graduates? competencies. 3) The solutions taken by Special Job Fair of State Vocational High School 1 of Surakarta include motivating its students, improving visit intensities of companies to the school, and disseminating job vacancy information through SMS, and improving cooperation with stakeholders.Keywords: Special Job Fair, career decision-making, graduates, and Vocational High School